Packaging of Non-Coding RNAs into Herpesvirus Virions: Comparisons to Coding RNAs - Amen, Melanie A.; Griffiths, Anthony (Frontiers in Genetics, 2011)
The herpesviruses are a family of large DNA viruses capable of establishing lifelong infections. Recent reports have shown that herpesviruses package noncoding RNA into virions; this follows earlier observations showing that coding RNAs are detected in virions. Packaging RNAs allows for their function immediately after virus entry and in the absence of de novo transcription. Despite the collective understanding that RNAs are packaged into herpesvirus virions, many questions remain. This review will highlight what is known regarding packaged coding and noncoding RNAs and discuss their potential impact to virus biology.